Loudmouth George and the big race - Carlson, Nancy L. (Minneapolis, MN : Carolrhoda Books, 1983)
George brags, procrastinates, and offers excuses instead of training for the big race--much to his later embarrassment.
2.4
K-3
Keywords: Rabbits -- Juvenile fiction; Racing -- Juvenile fiction; Excuses -- Juvenile fiction; Rabbits -- Fiction; Racing -- Fiction; Excuses -- Fiction; Rabbits -- Fiction; Excuses -- Fiction; Running -- Fiction; Rabbits -- Fiction; Racing -- Fiction; Excuses -- Fiction; Picture books for children